Hubungan Paparan Kebisingan, Beban Kerja Mental, Dan Faktor Individu Dengan Stres Kerja Pada Pekerja Di PT. Duraquipt Cemerlang Tahun 2021 - Annur Aini Al Alief (2021)
Work stress is stress that closely related to the work environment that can cause discomfort so that it affects the productivity of a worker. Individual factors, noise that exceeds the threshold value, and excessive mental workload can cause work stress. The purpose of this research was to determine the relationship between noise exposure, mental workload, and individual factors with work stress on workers at PT. Duraquipt Cemerlang. This study is a quantitative study using a cross-sectional study design with a chi-square test (p < 0,05). The sample of this study amounted to 106 people using total sampling technique. This research instrument uses a sound level meter to measure noise levels, DASS-42 questionnaire to measure work stress levels, and NASA-TLX questionnaire to measure the mental workload. The results showed there was a correlation between education (p=0,033) and mental workload (p=0,011) with work stress, and there was no correlation between noise (p=0,570), age (p=0,429), years of service (p=0,273), and marital status (p=0,719) with work stress. The highest noise intensity was found in the sandblasting area (87,3 dBA). In order to decrease work stress, the company should provide education about the prevention and control of work stress and provide service consultations for workers.